The Undecided Space of Ethics in Organizational Surveillance - Carl Rhodes (Organization Studies, 2010)
While much contemporary organizational research has highlighted how surveillance and self-surveillance are dominant modes of attempting subjective control in organizations, in this article we consider whether ‘being seen’ harbours the potential to also engender an ethics that motivates care for self and other. This ethics resides in an ‘undecided space’— one where individual conduct and subjectivity are not decided by surveillance-based discipline but performed by active subjects in interaction with each other in relation to that discipline. We draw on fieldwork conducted in the spinal unit of a major hospital to explore and demonstrate the instability of the association between discipline and surveillance in organizational life. The article provides an account of how a video-based intervention in the hospital led to alternative conducts and outcomes. We consider examples of in situ practice that show clinicians being dynamically attuned to one another in response to the video study. The contribution of the article is to demonstrate and illustrate how emergent subjectivity and interaction can result from such video ‘surveillance’. We conclude that ‘being seen’ can intensify mutual attentiveness to the point where interaction affords an ethic of care for self and other.